SAT0493 The Relation of Age, Bone Microarhitecture Index (TBS), and Bone Mineral Density (BMD) in Healthy Women in Menopause. (10th June 2014) - Novkovic, S.; Marinkovic, G.; Prodanovic, S.; Panic, M.; Terek, M.
Abstract : Objectives: To assess the relationship between age, the value of TBS and BMD in healthy postmenopausal women. Methods: In a cross sectional study including 257 healthy menopausal women, who underwent osteodensitometric (DXA) examination of the lumbar (L) spine and hip, with TBS score the L spine measured. The survey excluded all subjects with risk factors that could affect bone microarchitecture (steroids, previous fractures, systemic disease, excessive use of alcohol and cigarettes, as well as the use of drugs with a negative impact on bone metabolism). Statistical analysis was performed in SPSS system, appropriate statistical methods. Results: The average age of patients was 64.3±7.9 years. The average value of L spine BMD was 0.859±0.153 g/cm 2, while average hip BMD was 0.795±0.123 g/cm 2 . The mean value of TBS was 1.223±0.101. There was a significant positive correlation between the TBS and L spine BMD (r =0.487, p<0.001) and between the TBS and the hip BMD (r =0.292, p<0.001). A significant negative correlation was observed between age and TBS (ρ = -0.218, p<0.001), as well as the age and the BMD of the hip (ρ = -0.201, p<0.001), while the age and L spine BMD were not significantly correlated (ρ = -0.003, p=0.959). Conclusions: Any change in bone mineral density of the L spine and hip causes a change in the index of bone microarchitecture in the same direction. A reduction in the value of the bone microarchitecture index and bone mineral density of the hip is connected with aging. There was no significant variation in bone mineral density at L spine with age, which may indicate the progression of degenerative changes of the spine. TBS is an independent parameter, which has the potential diagnostic value itself, not taking into account the BMD. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2996